Composite particle as well as preparation method and application thereof

Composite particles are prepared by reactions of polyvinyl alcohol, phenyl rubber and benzene ring-containing crosslinking agent, and filled with waste rubber powder, which solves the problem of poor stability of existing water plugging agents in high temperature and high salt environments, and achieves low cost, Efficient water blocking effect and reduce environmental pollution, suitable for deep reservoir development.

CN119144105AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310703603.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The existing composite rubber powder granular plugging agent has poor stability in high temperature and high salt environments, high production costs, complex processes, and difficult to achieve deep-driving and driving effect, and there are environmental pollution problems.

Method used

The composite particles are prepared by reacting polyvinyl alcohol, phenyl rubber and benzene-containing ring crosslinking agent under the action of a catalyst, and filled with waste phenyl rubber powder, and modified by surfactant to form a water blocking agent that is resistant to high temperature and high salt. .

Benefits of technology

It reduces production costs, simplifies the process flow, improves the high-temperature and high-salt resistance and toughness of the particles, achieves effective water blocking effect in a high-temperature and high-salt environment, reduces environmental pollution, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144105A_ABST
    Figure CN119144105A_ABST
Patent Text Reader

Abstract

The invention provides a composite particle as well as a preparation method and application thereof. The composite particles are obtained by reacting polyvinyl alcohol with a cross-linking agent containing a benzene ring under the action of a catalyst and filling phenyl rubber. The composite particle provided by the invention can resist high temperature (not lower than 130 DEG C) and high salt (the degree of mineralization is not lower than 210000 mg / L), has self-healing ability, can be secondarily adhered at high temperature, has strong deformation ability after adhesion, and can realize deep fluid diversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oilfield water plugging and profile control, and in particular relates to a composite particle, a preparation method and application thereof. Background Art

[0002] With the continuous deepening of long-term water injection development in oil fields, data show that the average water content of my country's oil wells has exceeded 80%, and the water content of some oil wells has even reached more than 90%. The high-permeability channels for injected water in the oil reservoir continue to form, and the water output problem of oil wells is serious, resulting in low control of water injection wells, reduced oil recovery, serious scaling and corrosion of pipelines, and increased environmental pollution. Many problems have seriously restricted the efficient development of oil fields. Therefore, it is urgent to develop more efficient and high-quality oil field chemical water plugging and profile control agents.

[0003] After decades of development, chemical profile control and water plugging technology for oil fields at home and abroad has evolved from the initial cement slurry water plugging to resin water plugging and profile control, and then to the current mainstream water plugging agent - water-soluble polymer gel plugging agent. The varieties of oil field water plugging agents are becoming more and more diverse. Most oil fields have complex geological structures, serious heterogeneity, extremely strong conductivity of dominant flow channels, and most oil wells have high temperature and high salt characteristics. Affected by the effect of water plugging in fracture-cavity reservoirs, the existing profile control and water plugging material particles absorb water and expand quickly, so the injection depth is limited. After saturation with water, the granular materials are easy to break, and accurate plugging cannot be achieved, and the plugging effect is poor. In addition, the current water plugging technology has the problems of large dosage and high cost. Therefore, it is very necessary to carry out research on deep profile control and flooding technology, and at the same time develop new temperature-resistant and salt-resistant plugging agents for high-temperature and high-salt oil reservoirs.

[0004] Rubber powder composite particles are a kind of particle plugging agent with great potential. They can continue to play a role in drilling operation conditions with a wide temperature range during deep drilling, and have good plugging and filtration loss reduction effects. However, the current rubber powder composite particles have the following problems: in terms of performance, they are not resistant to heat and salt, and their stability deteriorates after being affected by the formation temperature, mineralization and pressure; in terms of production process, the production energy consumption is high, and the composite modification of waste rubber needs to react at a higher temperature. In some cases, it also needs to be mechanically stirred. The production equipment is complex and the initial investment is large, which is not conducive to promotion; in terms of production cost, the investment in the production line of waste rubber composite modified asphalt is high. Due to its poor storage stability and transportation stability, it is not suitable for long-term storage and long-distance transportation. The production site is relatively dense, which increases the production cost of the product. The entire production process is cumbersome, the cost is high, and it is difficult to industrialize.

[0005] Therefore, the existing composite rubber powder particle plugging agent still has a lot of room for improvement in technology and performance. The research and development of fracture-type deep flooding particles with excellent performance will undoubtedly have a positive effect on the development of fracture-cavity carbonate reservoirs and the ultimate economic benefits. Summary of the invention

[0006] One of the present invention provides a method for preparing composite particles, which comprises the following steps:

[0007] 1) mixing polyvinyl alcohol, phenyl rubber, a cross-linking agent containing a benzene ring and a first dispersant to obtain a first dispersion;

[0008] 2) mixing the first dispersion liquid and the second dispersant to obtain a second dispersion liquid;

[0009] 3) allowing the second dispersion to react under the action of a catalyst to obtain the composite particles.

[0010] According to a specific embodiment of the present invention, the total mass of the polyvinyl alcohol and the first dispersant is calculated as 100%, the mass of the polyvinyl alcohol is 5wt% to 10wt%, the mass of the phenyl rubber is 5wt% to 15wt%, and the mass of the benzene ring-containing cross-linking agent is 1wt% to 3wt%; and / or

[0011] The ratio of the total mass of the polyvinyl alcohol and the benzene ring-containing cross-linking agent to the volume of the catalyst is (6 to 13): (1 to 3); and / or

[0012] The mass of the second dispersant is 2 to 4 times the total mass of the polyvinyl alcohol and the first dispersant.

[0013] According to a specific embodiment of the present invention, the polyvinyl alcohol is selected from polyvinyl alcohol 1788 and / or polyvinyl alcohol 1799.

[0014] According to a specific embodiment of the present invention, the phenyl rubber is styrene-butadiene rubber;

[0015] Preferably, the phenyl rubber is styrene-butadiene rubber powder passing through an 80-mesh sieve.

[0016] In the present invention, the phenyl rubber is waste phenyl rubber powder, preferably styrene-butadiene rubber powder obtained by crushing waste tires made of styrene-butadiene rubber.

[0017] According to a specific embodiment of the present invention, the benzene ring-containing cross-linking agent is selected from at least one of terephthalaldehyde, diisopropylbenzene hydroperoxide, p-toluenesulfonic acid and p-toluenesulfonyl chloride; and / or

[0018] The catalyst is a strong inorganic acid;

[0019] Preferably, the catalyst is concentrated hydrochloric acid and / or concentrated sulfuric acid.

[0020] According to a specific embodiment of the present invention, the first dispersant is water.

[0021] According to a specific embodiment of the present invention, the second dispersant is a surfactant solution;

[0022] Preferably, the mass of the solvent in the surfactant solution is calculated as 100%, and the amount of the surfactant is 0.1wt% to 0.5wt%;

[0023] Preferably, the surfactant is at least one of Span-80, Span-60, Span-40 and polysorbate;

[0024] and / or

[0025] The solvent is at least one of carbon tetrachloride, propylene glycol, ethanol, ether and petroleum ether.

[0026] According to a specific embodiment of the present invention, the mixing temperature in step 1) is 85° C. to 95° C.; and / or

[0027] The mixing in step 2) is carried out by stirring; and / or the stirring speed is 350 rpm to 400 rpm; and / or

[0028] In step 3), the reaction is carried out at 25° C. to 40° C. for 2 h to 4 h.

[0029] According to a specific embodiment of the present invention, in step 3), the reaction product obtained by the reaction is filtered, washed with methanol and then washed with water to obtain the composite particles.

[0030] The second aspect of the present invention provides a composite particle prepared by the method described in the first aspect of the present invention;

[0031] Preferably, the particle size of the composite particles is 10 mesh to 60 mesh.

[0032] Application of the composite particles prepared by the method of the first invention or the composite particles of the second invention in water plugging and profile control in high-temperature and high-salinity fracture-cavity carbonate reservoirs, especially as plugging agents;

[0033] Preferably, the high temperature is not less than 130°C; and / or

[0034] The high salt has a mineralization of not less than 210000 mg / L.

[0035] Beneficial effects of the present invention:

[0036] In view of the problems of high production cost, complex process, too high temperature required for preparation, poor heat and salt resistance, and poor stability at high temperature in the composite rubber powder particle plugging agent in the prior art, the present invention provides a composite particle, a preparation method and application thereof. The composite particle is obtained by reacting polyvinyl alcohol and a cross-linking agent containing a benzene ring under the action of a catalyst and filling it with phenyl rubber.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The composite particles provided by the present invention are inexpensive to prepare and the raw materials are readily available, thus saving costs;

[0039] (2) It solves the environmental pollution problem caused by the direct disposal of waste phenyl rubber, and the resources are reused, turning waste into treasure;

[0040] (3) The waste phenyl rubber has a high filling content, the process equipment and steps are simple, the reaction conditions are simple, and it is easy to industrialize;

[0041] (4) Waste phenyl rubber is both a filler and a proppant, which plays a role of buffering and supporting, so that the particles have excellent toughness and good deformability. The density can be adjusted according to the proportion of rubber powder, making the particles easy to suspend and carry;

[0042] (5) The composite particles are resistant to high temperature (not less than 130°C) and high salt (mineralization not less than 210,000 mg / L), and the benzene ring-containing cross-linking agent and the phenyl rubber therein synergize to enhance the high temperature and high salt resistance of the composite particles;

[0043] (6) The composite particles can be adhered for a second time at high temperature, and have strong deformation ability after adhesion: in an aging experiment at 130°C and 210,000 mg / L mineralization, the composite particles provided by the present invention began to adhere when the aging time was 3 to 6 days, had moderate adhesion when the aging time was 27 to 36 days, and were completely adhered when the aging time was 43 to 54 days; after the aging time reached 60 days, there was no large-scale dissolution, the chemical stability was good, and it still had good elasticity, deformability and toughness, and could be used as a plugging agent to achieve deep liquid flow diversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The infrared spectra of polyvinyl alcohol and the composite particles prepared in Example 2 are shown, wherein (a) is the infrared spectrum of polyvinyl alcohol, and (b) is the infrared spectrum of the composite particles prepared in Example 2;

[0045] Figure 2 The thermogravimetric curves of the composite particles prepared in Example 1 and the ordinary particles prepared in Comparative Examples 1 and 2 are shown;

[0046] Figure 3The aging conditions of the composite particles prepared in Examples 1 to 4 and the ordinary particles prepared in Comparative Examples 1 and 2 at 130°C and 210000 mg / L mineralization are shown;

[0047] Figure 4 The adhesion of the composite particles prepared in Example 2 after aging for 60 days at 130° C. and 210,000 mg / L mineralization is shown. DETAILED DESCRIPTION

[0048] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0049] The styrene-butadiene rubber powder used in Examples 1 to 4 and Comparative Example 2 was obtained by crushing waste tires made of styrene-butadiene rubber and passing them through an 80-mesh sieve, and collecting the styrene-butadiene rubber powder that could pass through the 80-mesh sieve.

[0050] Example 1

[0051] 5 g of polyvinyl alcohol (PVA1799), 5 g of styrene-butadiene rubber powder and 1 g of terephthalaldehyde were added to 95 g of water, mixed at 95° C. for 2 h, and dispersed in 300 g of carbon tetrachloride containing 0.1 wt% Span-80 under vigorous stirring to prepare an oil-in-water dispersion system. The stirring speed was controlled at 350 rpm, and then 1 mL of concentrated hydrochloric acid was added as a catalyst. The mixture was reacted at 25° C. for 4 h to gradually form composite particles. The particles were filtered, the attached carbon tetrachloride was washed off with methanol, and then washed with water to obtain composite particles with a particle size mainly distributed between 10 and 60 meshes.

[0052] Example 2

[0053] 10g of polyvinyl alcohol (PVA1799), 15g of styrene-butadiene rubber powder and 3g of terephthalaldehyde were added to 90g of water, mixed at 95°C for 2h, dispersed in 200g of carbon tetrachloride containing 0.1wt% Span-80 under vigorous stirring to prepare an oil-in-water dispersion system, the stirring speed was controlled at 400rpm, and then 2mL of concentrated hydrochloric acid was added as a catalyst, reacted at 30°C for 3h, and composite particles were gradually formed. The particles were filtered, the attached carbon tetrachloride was washed off with methanol, and then washed with water to obtain composite particles with a particle size mainly distributed between 10 and 60 meshes.

[0054] Example 3

[0055] 10g of polyvinyl alcohol (PVA1788), 5g of styrene-butadiene rubber powder and 2g of terephthalaldehyde were added to 90g of water, mixed at 85°C for 2h, dispersed in 250g of carbon tetrachloride containing 0.1wt% Span-80 under vigorous stirring to prepare an oil-in-water dispersion system, the stirring speed was controlled at 350rpm, and then 2.5mL of concentrated hydrochloric acid was added as a catalyst, reacted at 30°C for 3h, and composite particles were gradually formed. The particles were filtered, the attached carbon tetrachloride was washed off with methanol, and then washed with water to obtain composite particles with a particle size mainly distributed between 10 and 60 meshes.

[0056] Example 4

[0057] 10g of polyvinyl alcohol (PVA1788), 10g of styrene-butadiene rubber powder and 2g of terephthalaldehyde were added to 90g of water, mixed at 85°C for 2h, dispersed in 300g of carbon tetrachloride containing 0.1wt% Span-80 under vigorous stirring to prepare an oil-in-water dispersion system, the stirring speed was controlled at 400rpm, and then 3mL of concentrated hydrochloric acid was added as a catalyst, reacted at 40°C for 2h, and composite particles were gradually formed. The particles were filtered, the attached carbon tetrachloride was washed off with methanol and then washed with water to obtain composite particles with a particle size mainly distributed between 10 and 60 meshes.

[0058] Comparative Example 1

[0059] Add 5g of polyvinyl alcohol (PVA1799) and 1g of terephthalaldehyde to 95g of water, mix at 95°C for 2h, and disperse them in 300g of carbon tetrachloride containing 0.1wt% Span-80 under vigorous stirring to prepare an oil-in-water dispersion system. The stirring speed is controlled at 350rpm, and then 1mL of concentrated hydrochloric acid is added as a catalyst. React at 25°C for 4h to gradually form composite particles. Filter, wash off the attached carbon tetrachloride with methanol and then wash with water to obtain ordinary particles.

[0060] Comparative Example 2

[0061] Add 5g of polyvinyl alcohol (PVA1799), 5g of styrene-butadiene rubber powder and 1g of glutaraldehyde to 95g of water, mix at 95°C for 2h, and disperse them in 300g of carbon tetrachloride containing 0.1wt% Span-80 under vigorous stirring to prepare an oil-in-water dispersion system. The stirring speed is controlled at 350rpm, and then 1mL of concentrated hydrochloric acid is added as a catalyst. React at 25°C for 4h to gradually form composite particles. Filter, wash off the attached carbon tetrachloride with methanol and then wash with water to obtain ordinary particles.

[0062] Test Example 1

[0063] An infrared spectrometer was used to measure the infrared spectra of polyvinyl alcohol and the composite particles prepared in Examples 1 to 4. Here, the infrared spectra of polyvinyl alcohol and the composite particles prepared in Example 2 were taken as an example for analysis.

[0064] Figure 1 The infrared spectra of polyvinyl alcohol and the composite particles prepared in Example 2 are shown, wherein (a) is the infrared spectrum of polyvinyl alcohol, and (b) is the infrared spectrum of the composite particles prepared in Example 2. It can be seen that the -OH stretching vibration band of polyvinyl alcohol is located at 3442 cm -1 The spectrum of the composite particles is at 871 cm -1 (for p-disubstituted benzene), 1100cm -1 A new absorption band appears at (C—O—C group), indicating that in the composite particles prepared in Example 2, a chemical cross-linking reaction occurs between polyvinyl alcohol and terephthalaldehyde.

[0065] The infrared spectra of the composite particles prepared in Examples 1, 3 and 4 are Figure 1 Similar to (b) in the above, in the composite particles prepared in Examples 1, 3, and 4, polyvinyl alcohol and terephthalaldehyde underwent chemical crosslinking reactions.

[0066] Test Example 2

[0067] The thermogravimetric curves of the composite particles prepared in Examples 1 to 4 and the ordinary particles prepared in Comparative Examples 1 and 2 were measured using a thermogravimetric analyzer to evaluate the thermal stability of the composite particles and the ordinary particles. The thermogravimetric curves of the composite particles prepared in Example 1 and the ordinary particles prepared in Comparative Examples 1 and 2 were taken as examples for analysis.

[0068] Figure 2 The thermogravimetric curves of the composite particles prepared in Example 1 and the ordinary particles prepared in Comparative Examples 1 and 2 are shown. As can be seen from the figure, the ordinary particles prepared in Comparative Example 1 without adding styrene-butadiene rubber powder begin to lose weight at about 250°C, remain stable when the temperature rises to 450°C, maintain a mass of about 5%, and the corresponding weight loss rate is 95%. The ordinary particles prepared in Comparative Example 2 with glutaraldehyde as the crosslinking agent begin to lose weight at about 230°C, remain stable when the temperature rises to 500°C, maintain a mass of about 10%, and the corresponding weight loss rate is 90%. The composite particles prepared in Example 1 with terephthalaldehyde as the crosslinking agent containing benzene rings and filled with styrene-butadiene rubber powder begin to decompose at above 300°C, and the weight loss ends when the temperature rises to 480°C, and the mass is maintained at about 20%, and the corresponding weight loss rate is 80%. Comparing the thermogravimetric curves of the three, it can be seen that the thermal stability of the composite particles prepared in Example 1 is significantly better than that of the ordinary particles prepared in Comparative Examples 1 and 2. The terephthalaldehyde and phenyl rubber powder in the composite particles synergistically enhance the thermal stability of the composite particles and make them have good temperature resistance.

[0069] Test Example 3

[0070] The composite particles prepared in Examples 1 to 4 and the ordinary particles prepared in Comparative Examples 1 and 2 were subjected to a high temperature and high salt aging experiment at 130° C. and 210,000 mg / L. The specific steps are as follows:

[0071] 5 g of the composite particles prepared in Examples 1 to 4 and the ordinary particles prepared in Comparative Examples 1 and 2 were respectively placed in a pressure-resistant bottle containing 20 mL of Tahe formation simulated water with a mineralization of 210,000 mg / L, sealed, and placed in an aging box at 130° C. for 60 days. For ordinary particles that have achieved complete adhesion within 30 days, the experiment was stopped after the aging time reached 30 days, and the state of the ordinary particles after adhesion was observed and recorded. The experimental results of the composite particles and the ordinary particles are as follows: Figure 3 shown.

[0072] The aging conditions of the composite particles prepared in Examples 1 to 4 and the ordinary particles prepared in Comparative Examples 1 and 2 are as follows: Figure 3 As shown. Figure 3 It can be seen that at 130°C and 210,000 mg / L mineralization: the composite particles prepared in Example 1 begin to stick when the aging time is about 3 days, reach moderate adhesion when the aging time is about 27 days, and are completely adhered when the aging time is about 43 days; the composite particles prepared in Example 2 begin to stick when the aging time is about 6 days, reach moderate adhesion when the aging time is about 36 days, and are completely adhered when the aging time is about 54 days; the composite particles prepared in Example 3 begin to stick when the aging time is about 4 days, have moderate adhesion when the aging time is about 29 days, and are completely adhered when the aging time is about 48 days; the composite particles prepared in Example 4 begin to stick when the aging time is about 4 days, reach moderate adhesion when the aging time is about 33 days, and are completely adhered when the aging time is about 52 days. The ordinary particles prepared in Comparative Example 1 began to stick after aging for 1 day at 130°C and 210000 mg / L mineralization, and the aging time was about 7 days to reach moderate adhesion, and the aging time was about 13 days to reach complete adhesion. The ordinary particles prepared in Comparative Example 2 began to stick after aging for about 1 day at 130°C and 210000 mg / L mineralization, and the aging time was about 6 days to reach moderate adhesion, and the aging time was about 9 days to reach complete adhesion. The above results prove that the composite particles prepared in Examples 1 to 4 can withstand high temperature and high salt, and have good self-healing ability at high temperature and high mineralization.

[0073] Since the ordinary particles prepared in Comparative Examples 1 and 2 had too fast adhesion speed, they were completely adhered before the aging time reached 30 days. The experiments of Comparative Examples 1 and 2 were stopped after the aging time reached 30 days, and the state of the ordinary particles prepared in Comparative Examples 1 and 2 after complete adhesion was observed. It was found that the ordinary particles prepared in Comparative Example 1 could not be stretched after complete adhesion, and had poor mechanical properties, poor chemical stability, and poor high temperature and high salt resistance; the ordinary particles prepared in Comparative Example 2 were completely dissolved after reaching complete adhesion within 30 days of aging at 130°C and 210000mg / L mineralization, and had poor chemical stability and poor high temperature and high salt resistance.

[0074] After the aging time reaches 60 days, the composite particles prepared in Examples 1 to 4 are taken out and it is found that the four composite particles do not dissolve in large quantities after being completely adhered, have good chemical stability, and still have good elasticity, deformability and toughness. Figure 4 That is, the composite particles prepared in Example 2 are completely adhered and taken out after the aging time reaches 60 days. It can be seen that after complete adhesion, the composite particles still maintain a certain spherical shape, and there is no excessive adhesion or large-scale dissolution. From the formula point of view, compared with Example 1, the raw material of Comparative Example 1 lacks styrene-butadiene rubber powder, and the raw material of Comparative Example 2 replaces the benzene ring-containing cross-linking agent terephthalaldehyde with glutaraldehyde, which is manifested as the adhesion speed of the ordinary particles prepared in Comparative Examples 1 and Comparative Examples 2 is too fast, and the chemical stability, mechanical properties, and high temperature and high salt resistance are poor. This shows that in the method for preparing composite particles provided by the present invention, the cross-linking agent containing a benzene ring and the phenyl rubber used synergistically enhance the performance, which helps to achieve good high temperature and high salt resistance of the composite particles.

[0075] In summary, the composite particles provided by the present invention are resistant to temperature and salt (specifically 130°C and 210,000 mg / L mineralization), have self-healing ability, can be re-adhered at high temperatures, have strong deformation ability, and can be used as a plugging agent to achieve deep liquid flow diversion.

[0076] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A method for preparing composite particles, comprising the following steps: 1) mixing polyvinyl alcohol, phenyl rubber, a cross-linking agent containing a benzene ring and a first dispersant to obtain a first dispersion; 2) mixing the first dispersion liquid and the second dispersant to obtain a second dispersion liquid; 3) allowing the second dispersion to react under the action of a catalyst to obtain the composite particles.

2. The method according to claim 1, characterized in that The total mass of the polyvinyl alcohol and the first dispersant is calculated as 100%, the mass of the polyvinyl alcohol is 5wt% to 10wt%, the mass of the phenyl rubber is 5wt% to 15wt%, and the mass of the benzene ring-containing cross-linking agent is 1wt% to 3wt%; and / or The ratio of the total mass of the polyvinyl alcohol and the benzene ring-containing cross-linking agent to the volume of the catalyst is (6 to 13): (1 to 3); and / or The mass of the second dispersant is 2 to 4 times the total mass of the polyvinyl alcohol and the first dispersant.

3. The method according to claim 1 or 2, characterized in that: The polyvinyl alcohol is selected from polyvinyl alcohol 1788 and / or polyvinyl alcohol 1799.

4. The method according to any one of claims 1 to 3, characterized in that The phenyl rubber is styrene-butadiene rubber; Preferably, the phenyl rubber is styrene-butadiene rubber powder passing through an 80-mesh sieve.

5. The method according to any one of claims 1 to 4, characterized in that The benzene ring-containing cross-linking agent is selected from at least one of terephthalaldehyde, diisopropylbenzene hydroperoxide, p-toluenesulfonic acid and p-toluenesulfonyl chloride; and / or The catalyst is a strong inorganic acid; Preferably, the catalyst is concentrated hydrochloric acid and / or concentrated sulfuric acid.

6. The method according to any one of claims 1 to 5, characterized in that The first dispersant is water.

7. The method according to any one of claims 1 to 6, characterized in that The second dispersant is a surfactant solution; Preferably, the mass of the solvent in the surfactant solution is calculated as 100%, and the amount of the surfactant is 0.1wt% to 0.5wt%; Preferably, the surfactant is at least one of Span-80, Span-60, Span-40 and polysorbate; and / or The solvent is at least one of carbon tetrachloride, propylene glycol, ethanol, ether and petroleum ether.

8. The method according to any one of claims 1 to 7, characterized in that The mixing temperature in step 1) is 85°C to 95°C; and / or In step 3), the reaction is carried out at 25° C. to 40° C. for 2 h to 4 h.

9. A composite particle prepared by the method according to any one of claims 1 to 8; Preferably, the particle size of the composite particles is 10 mesh to 60 mesh.

10. Use of the composite particles prepared by the method according to any one of claims 1 to 8 or the composite particles according to claim 9 in water plugging and profile control in high-temperature and high-salinity fracture-cavity carbonate reservoirs, especially as plugging agent; Preferably, the high temperature is not less than 130°C; and / or The high salt has a mineralization of not less than 210000 mg / L.

Citation Information

Patent Citations

  • Multi-crosslinking polymer gel profile control agent and application thereof

    CN111286311A

  • Slow-crosslinking temperature-resistant salt type high-strength gel, and preparation method and application thereof

    CN111808585A

  • Seawater-based polyacrylamide high-temperature gel profile control system

    CN113249103A

  • Porous cross-linked polyvinyl alcohol particles, process for producing the same, and separating agent composed of the same

    US4863972A